Energy Evaluation of the Municipal Solid Waste Pyrolysis - Wagnerova, Emilia; Uricek, David (Communications - Scientific letters of the University of Zilina, 2006)
This contribution deals with possibilities of using pyrolysis as a method for municipal solid waste (MSW) disposal. Taking into account the possibilities of MSW separation, specific sorts of wastes were selected and subjected to laboratory experiments. The main aim of experimental measurements was to determine the distribution of the caloric value of an original sample in the products of pyrolysis. The aim of this research was to determine the energy content of selected MSW sorts and to recommend the method of their thermal disposal.